Blue Energy Spearheading the Energy Transition: The Case of Crete - Stančin, Hrvoje; Pfeifer, Antun; Perakis, Christoforos; Stefanatos, Nikolaos; Damasiotis, Marko; Magaudda, Stefano; Di Pietrantonio, Federica; Mikulčić, Hrvoje (Frontiers in Energy Research, 2022)
Decarbonization of remote or isolated island communities represents a significant challenge nowadays. Nevertheless, the environmental, economic, and social benefits seek more attention. Lately, blue energy sources, particularly offshore wind power, are gaining momentum to take the lead in the energy transition process, simultaneously offering numerous benefits for local communities and potential investors. In this research, offshore wind power is considered the main driver of the energy transition for the case of the island of Crete. The energy systems’ development scenarios are developed using an energy planning model EnergyPLAN, starting from a reference model developed for the year 2017. Since the island was recently isolated without connections to the mainland grid, integrating renewable energy sources was a challenging task that led to poor energy potential exploitation. The decarbonization of the power generation sector by offshore, onshore wind, and photovoltaics can only partially reduce the import dependence on fossil fuels. At the same time, more significant efforts are expected in the transport and industry sectors. With the operational interconnections, 300 MW of offshore wind capacities can be deployed, averaging annual electricity production of 1.17 TWh, satisfying around 70% of total electricity demand.